(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Health education using lectures can be useful, but also boring to communities. A new strategy is needed that can be enjoyable, without requiring significant additional resources. As part of a nationwide social-marketing campaign, special events to promote Vitamin A Supplementation (VAS) in Indonesia have employed a new strategy called “Edutainment”. Goal: To educate specific target groups on health issues, within an entertaining environment, so that learning is more enjoyable. Methodology: “Edutainment” combines health “education” with “entertainment”. A day-long “Edutainment” event may include: health competitions, talk-shows with quizzes/prizes, games, door prizes, and announcing winners at the end of the event. The activities support the event’s main theme. Local sponsors cover most costs. A popular personality (“icon”) like an artist or government official can participate, and should be chosen to attract specific target groups. Radio announcements or strategically placed fliers promote the event beforehand. Experience to date: Twelve HKI/IBB (Yayasan Ibu, Bayi, dan Balita) health fairs were conducted from 2002-04 in cities across Indonesia. 1.000 – 2.000 participants attended each fair, which lasted approximately 6 hours each. Frequently participants stayed in the event area even after the event ended. Competitions were the most popular activity, since participants wanted to win prizes. Sponsors were given a booth and promoted their products throughout the day. Conclusion: “Edutainment” is a good strategy to deliver health education to specific target groups in an entertaining atmosphere. “Edutainment” events are ideal when resources for health promotion/education are limited, since organizers receive outside sponsorship to cover most costs.